ANALISIS KEDUDUKAN ALQURAN, SUNNAH DAN AKAL SEBAGAI SUMBER HUKUM ISLAM - Riswandi, Dendi (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2024)
ABSTRACT The division of Islamic legal sources has several different placement sequences. For example, the sequence of sources of Islamic law that have been agreed: the Qur’an, Sunnah, Ijma ’and Qiyas. Some other scholars divide the source of Islamic law is divided into two namely: Naqli and Aqli. Naqli consists of the Qur’an and Sunnah, while Aqli consists of Ijma and Qiyas. On the other hand, putting the Qur’an and Sunnah alone as a source of Islamic law and some putting reason as the first source of Islamic law before the Qur’an and Sunnah became its own problems. Mahmud Syaltut said that the source of Islamic law there are three, namely the Qur’an, Sunnah and Ijtihad bi ra’yi (reason). The understanding of Mahmud Syaltut’s legal sources departs from the relation between text and context. The Qur’an and Sunnah are intended as a direct approach to the text. While ra’yu is ijtihad to the various problems that are not found in the texts which are then practiced through the method of ijma ’, the school of sahabi, qiyas, istihsan, istihsab, maslahah mursalah,’ urf, Sadd al-dzariah, Syar’u man qoblana . According to Harun Nasution, explaining the position of reason and revelation is the intellect of knowing the existence of God, knowing that man is obliged to worship and thank him but reason is incapable of knowing all the attributes of God and can not know the way to worship him , it is the revelation that explains to the mind how to worship and thank God. And reason also can not know the details of good and evil. Here is the function of revelation that reinforces the opinion of reason through the sacred and absolute nature contained in the revelation. This study aims to explain the concept of the order of sources of Islamic law so that readers can understand various differences. The approach of qualitatif and this research is library research approach. The method used is the method of description - analysis, which is expected to explain the position of Islamic legal sources. In the author’s analysis, the Qur’an has clearly explained in several verses that reason has a very important role given by Allah as a gift and mercy to increase piety to Him. So the position of reason becomes a way to help humans, especially mujtahids in deciding contemporary legal cases as long as they do not contradict the Qur’an and Sunnah. In this day and age the process of ijtihad is still very wide open because times are constantly changing. Nevertheless The application of ijtihad does not apply to individual fardi ijtihad) but to jama’i (collective) ijtihad. Because modern science is increasingly complex, the mastery of all fields by a mujtahid is very difficult, so it can be united according to experts in their respective fields to jointly determine legal issues. Keywords: Alqur’an, Sunnah, Akal, Source of Islamic Law,.